Microfluidic chip development for bio-defence application - Sim, Bernard Wee Jun (2014)
The developments in Microfluidic applications have enabled a breakthrough in the creation of Lab-on-chip devices which allows rapid bio-chemical analysis for fast diagnostics. These chips give significant benefits in terms of low sample volume, less sample wastage, fast analysis time, cost effectiveness as well as the possibility of developing different diagnostic on different chips all at one go. Hence, in this report, it focuses on the development of a novel idea of using a magnetic membrane to create a micromixer which could be used to introduce a turbulent flow to a fluid enhancing the mixing process.